2018
DOI: 10.4314/jfas.v9i4s.43
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of ambient air pollution pattern in Shah Alam, Selangor, Malaysia

Abstract: This study implements the statistical analysis to establish the association between air pollution trends with the industrial activities in Shah Alam, Selangor. PCA used to identify significant parameters contributing to air pollution and it sources of pollutions, whereas SPC used to determine the pattern and contribution each of most significa area and Spearman Correlation used to determine the relatio meteorological factors. The result identified the major possible sources of air pollution were 38.3% and 32.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The highest reading of PM10 were recorded at 319.750µg/m 3 on 17 th December 2015. A previous study demonstrated that the pattern of PM10 was similar as the pattern of API [26]. The high volume of PM10 in Kuching, Sarawak resulted from the vehicles emission and forest burning for agriculture purposes [27][28].…”
Section: Pattern Of the Major Air Pollutants And Air Pollutant Index mentioning
confidence: 91%
See 2 more Smart Citations
“…The highest reading of PM10 were recorded at 319.750µg/m 3 on 17 th December 2015. A previous study demonstrated that the pattern of PM10 was similar as the pattern of API [26]. The high volume of PM10 in Kuching, Sarawak resulted from the vehicles emission and forest burning for agriculture purposes [27][28].…”
Section: Pattern Of the Major Air Pollutants And Air Pollutant Index mentioning
confidence: 91%
“…Moreover, the elevation of PM10 concentration was related to the occurrence of transboundary haze pollution from Indonesia due to Sumatra bush burning for agriculture purposes [5]. The smoke then travel to other countries and affected the air quality in those travelled areas [26]. In addition, the emission of PM10 was also associated with agriculture activities at the area.…”
Section: Identification Of the Most Significant Parameters That Affecmentioning
confidence: 99%
See 1 more Smart Citation
“…The Air Quality [17][18][19][20][21][22][23][24][25] Guidelines set for the first time a guideline value for particulate matter and the aim of the guidelines is to achieve the lowest concentrations of pollutant in atmosphere as possible [11].…”
Section: Review Of Literaturesmentioning
confidence: 99%
“…and each component has its own pattern of contribution hours to the variation. To visualize the pattern, line charts were constructed using the PCA [26][27][28][29][30][31] factor loading as depicted in Fig. 4.…”
Section: Diurnal Levels Of O 3 Concentrationmentioning
confidence: 99%